PENGEMBANGAN MEDIA POP UP BOOK BERBASIS PjBL UNTUK MENINGKATKAN KETERAMPILAN BERPIKIR KRITIS SISWA SEKOLAH DASAR - Emilia Sari; Nurlaksana Eko Rusminto; Dwi Yulianti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to develop Pop Up Book media based on Project Based Learning (PjBL) to improve critical thinking skills of grade IV elementary school students on main ideas and supporting ideas in Indonesian language learning. The research method uses Research and Development (R&D) with the Borg and Gall model modified into seven stages, including information gathering, planning, initial product development, expert testing (material, media, language), practicality testing, main trial, and product revision. The research subjects consisted of 28 experimental class students and 28 control class students at SDN 1 Way Kandis, Bandar Lampung. Data were collected through questionnaires, observations, tests, and documentation, then analyzed descriptively quantitatively and qualitatively. The results of expert validation showed that the media was very feasible with a score of 88.42% material experts, 70.66% media experts, and 81.81% language experts. Practicality test by teachers obtained an average score of 97% (very practical). The media proved effective in improving students' critical thinking skills by 24.67%, with the N-Gain value of the experimental class (0.6045) higher than the control class (0.4925). The independent sample t-test showed a significant difference (sig. 0.034 <0.05) between the post-test of the two groups. The conclusion of the study states that Pop Up Book media based on Project Based Learning (PjBL) is feasible, practical, and effective as an innovative learning media to improve critical thinking skills of elementary school students.